DOES THE WORLD NEED MORE CANADA? LEGAL MULTILINGUALISM AND STRATEGIC PLURALISM - Leung, Janny (Revue de droit de l'Université de Sherbrooke, 2017)
Canada has a global reputation as a diverse and tolerant country, with linguistic duality being a proud marker of its pluralistic society and a defining feature of its nationhood. This paper evaluates the extent to which legal bilingualism as practiced in Canada provides a good and practicable model to the rest of the world, which has seen a rise in legal bilingual and multilingualism in recent decades. Through tracing convergent and divergent practices across jurisdictions, the paper probes whether the apparent embrace of linguistic diversity, in Canada and beyond, safeguards justice and liberty. By providing a realistic understanding of legal bilingual or multilingualism in the world today, this paper cautions against excessive optimism that is sometimes expressed towards the emancipatory potential of official linguistic pluralism.